15N fate in maize cropping system in response to black soil fertility improvement in China. (25th September 2021) - Fu, HaiMei; Duan, YingHua; Zhu, Ping; Gao, HongJun; Xu, MingGang
Abstract: Applications of high amounts of nitrogen (N) fertilizer are essential for obtaining sustainable maize ( Zea mays L.) yields but also result in low N‐use efficiency (NUE) and cause a series of environmental problems. To optimize fertilizer management, it is necessary to determine the effects of soil fertility improvement on NUE and the fate of N fertilizer. In this study, we conducted a 15 N tracer pot experiment involving five different fertilizer treatments in soils with five different total organic carbon levels under field conditions. The average NUE ranged from 36 to 56% 15 N‐urea and 0.1 to 0.2% residual N in the first and second seasons. The N retained in the soil ranged from 10 to 28%, and the N lost to water and the atmosphere ranged from 29 to 39% in the five soils. Compared with that in the low‐fertility soils, NUE in the high‐fertility soils was 20–45% greater, and N loss was 1 –6% lower. The results showed that higher soil fertility corresponded to higher NUE and lower N loss. We suggest that although the local customary N fertilizer application rate (N3; 165 kg N/ha) in the study area is reasonable for low‐fertility soils, after soil fertility improvements, an approximately 50% reduction of N fertilizer should be implemented. Core Ideas: Five different fertility black soils were collected to analyze the fate of N fertilizer. The N‐use efficiency of maize increased by 20–45% with the improvement of black soil fertility. The N loss decreased by 1–6% after the soil fertility improved in maize cropping system. Fifty percent reduction of N fertilizer should be implemented in high fertility soils in northeast China.